Research progress in cell therapy for oral diseases: focus on cell sources and strategies to optimize cell function - Wang, Jing; Zhao, Zeqing; Yang, Kai; Bai, Yuxing (Frontiers in Bioengineering and Biotechnology, 2024)
In recent years, cell therapy has come to play an important therapeutic role in oral diseases. This paper reviews the active role of mesenchymal stem cells, immune cell sources, and other cells in oral disorders, and presents data supporting the role of cell therapy in oral disorders, including bone and tooth regeneration, oral mucosal disorders, oral soft tissue defects, salivary gland dysfunction, and orthodontic tooth movement. The paper will first review the progress of cell optimization strategies for oral diseases, including the use of hormones in combination with stem cells, gene-modified regulatory cells, epigenetic regulation of cells, drug regulation of cells, cell sheets/aggregates, cell-binding scaffold materials and hydrogels, nanotechnology, and 3D bioprinting of cells. In summary, we will focus on the therapeutic exploration of these different cell sources in oral diseases and the active application of the latest cell optimization strategies.